Hope : Philosophizing from multi horizons - Ivan Dsouza Ed (Eluru Association of Christian Philosophers of India, 2025)
HOPE: Philosophizing from Multi-horizons comprises the proceedings of the 47th National Annual Research Seminar of the Association of Christian Philosophers of India (ACPI), convened at St Joseph$1 (Bs Interdiocesan Seminary, Jeppu, Mangalore, from 19 to 21 October 2024. In a world shadowed by despair, darkness, desolation, and despondency, hope emerges as the force that lends meaning and direction to human existence. The natural world itself yearns for this hope, inviting us to commit to ecological preservation, sustainable development, and a renewed harmony with Mother Earth. Given the pressing need of hope for humanity and the world at large, this volume sheds light on its significance in the context of the Jubilee Year 2025$1 (Ba Year of Hope. The contributions gathered here are not just a set of academic essays; they form a symphonic dialogue across traditions, disciplines, and lived realities. They explore existential foundations, metaphysical frameworks, psycho-somatic dimensions, social and political praxis, transformative and integrative visions of hope. Each essay has its own insights and reflections, yet together they broaden our understanding of what it means to hope in our time. These discourses invite readers to discern the signs of hope and to derive or infuse hope into their human, cosmic, and divine realmss
Keywords: Psycho Somatic Dimensions; Ethics of Hope; ACPI Annual Research Seminar